Effect of Industrial and Domestic Processing Techniques On the DNA Degradation of Anchovy - Elif Tuğçe Aksun Tümerkan (Turkish Journal of Agriculture: Food Science and Technology, 2021)
Food fraudulent activities have become a serious issue over the world recently. Seafood products have trading and profitable potential in Turkey owing to the abundance of fisheries and other species. While morphological features are commonly used for species identification in raw seafood products, this identification does not meet the correct classification in cryptic species and processed seafood products. Molecular techniques have been utilized for species authentication in processed seafood items successfully. In this study, the effect of different processing techniques on the DNA quality and DNA degradation isolated from raw and processed anchovy was investigated. Anchovy is one of the important species in both fisheries activities and processing and consumption in Turkey. For this aim, DNA was isolated from processed anchovy groups and un-processed anchovy groups as control by the same extraction methods and the quality of DNA was compared among the groups. The most common processing techniques, frying, baking, smoking, roasting, baking and grilling were applied to anchovy. The results revealed that not only different thermal processing but also treatment with acid and salt cause DNA degradation and quality loss of DNA parameters which are essential for authentication of species and traceability for public health.